Branched‐Tail Lipid Nanoparticles Potently Deliver mRNA In Vivo due to Enhanced Ionization at Endosomal pH. Issue 6 (13th January 2019) - Hajj, Khalid A.; Ball, Rebecca L.; Deluty, Sarah B.; Singh, Shridhar R.; Strelkova, Daria; Knapp, Christopher M.; Whitehead, Kathryn A.
Abstract: The potential of mRNA therapeutics will be realized only once safe and effective delivery systems are established. Unfortunately, delivery vehicle development is stymied by an inadequate understanding of how the molecular properties of a vehicle confer efficacy. Here, a small library of lipidoid materials is used to elucidate structure–function relationships and identify a previously unappreciated parameter—lipid nanoparticle surface ionization—that correlates with mRNA delivery efficacy. The two most potent materials of the library, 306O10 and 306Oi10, induce substantial luciferase expression in mice following a single 0.75 mg kg −1 mRNA dose. These lipidoids, which have ten‐carbon tails and identical molecular weights, vary only in that the 306O10 tail is straight and the 306Oi10 tail has a one‐carbon branch. Remarkably, this small difference in structure conferred a tenfold improvement in 306Oi10 efficacy. The enhanced potency of this branched‐tail lipidoid is attributed to its strong surface ionization at the late endosomal pH of 5.0. A secondary lipidoid library confirms that Oi10 materials ionize more strongly and deliver mRNA more potently than lipidoids containing linear tails. Together, these data highlight the exquisite control that lipid chemistry exerts on the mRNA delivery process and show that branched‐tail lipids facilitate protein expression in animals. Abstract : Lipid nanoparticles (LNPs) are an exciting tool to deliver messenger RNA (mRNA) drugs that have the potential to treat any disease caused by faulty protein expression. This work describes the exquisite control that branched lipid tails exert on the mRNA delivery process by modulating LNP surface ionization at endosomal pH.